How Working in Local TV News Affects Journalists' Personal Lives - (:unkn) unknown (My University, 2017)
This study uses participant observation and interviews to determine how working in local television news affects journalists’ personal lives. Twenty-eight journalists from a top 50 Midwestern station were interviewed. The inductive research data is organized into three themes: 1) Schedules 2) Family, friends and relationships 3) Moving. A personal narrative of the researcher’s experience working part-time ties each theme together.
Keywords: journalism; local television news; market size; television station; work-life balance; work schedule